La mustia hilachosa - Gálvez E., Guillermo E.; Guzmán, P.; Castaño, M. (International Center for Tropical Agriculture, 1980)
Web blight, caused by the fungus Thanatephorus cucumeris, is prevalent in tropical regions with high to moderate temp and RH; more than 200 plant species serve as hosts to this pathogen. Hyphae can grow rapidly over healthy tissue of leaves, flowers, petioles and pods. For efficient control, the use of disease-free seeds, elimination of harvest debris, crop rotation, the use of adequate chemical products and the use of resistant var. are recommended. The symptoms and damage caused by the disease are illustrated in color. (CIAT)